Safety and Feasibility Analysis of Laparoscopic Lymphadenectomy in Pelvic Gynecologic Malignancies: A Prospective Study. Issue 9 (1st November 2015) - Benito, Virginia; Romeu, Silvia; Esparza, Miriam; Carballo, Sonia; Arencibia, Octavio; Medina, Norberto; Lubrano, Amina
Abstract : Objective: The aims of this study were to evaluate prospectively the safety and feasibility of laparoscopic lymphadenectomy in gynecologic oncology and to analyze risk factors associated with surgical adverse events. Materials and Methods: This study included 444 consecutive laparoscopic lymphadenectomy procedures conducted in 358 consecutive gynecologic oncology patients, between 2007 and 2014. Surgical adverse events were classified into intraoperative, early postoperative (≤6 weeks after surgery), and late postoperative (>6 weeks after surgery). Logistic regression analysis was used to assess the independent effects of different variables on the probability of complications. Differences were considered to be statistically significant for P values less than 0.05. Results: Two hundred forty-four pelvic lymphadenectomy and 200 aortic lymphadenectomy procedures were carried out during the studied period. All pelvic lymphadenectomy procedures were conducted with a transperitoneal approach, whereas 94.5% of aortic lymphadenectomy procedures were conducted with an extraperitoneal approach. A total of 52.2% of tumors were found to originate in the cervix, 38% in the endometrium, 6.4% in the ovary, 2.8% were sarcoma, and 0.6% were in a different region. The laparotomy conversion rate was 2.8%. The rate of intraoperative adverse events was 1.9%, the most frequent ones being vascular injuries followed by ureteral, bowel, or neurologic injuries. The rate of early-postoperative adverse events was 3.3%, the most frequent one being incisional hernia followed by hemoperitoneum, pelvic abscess, intestinal injury, and paralytic ileus. One patient with endometrial cancer died after surgery due to sepsis of unknown origin. The rate of late-postoperative adverse events was 3.6% and consisted mainly of symptomatic lymphocele or lymphedema. A logistic regression analysis showed that factors associated with increased risk of lymphadenectomy surgical complications were surgical bleeding and operative time (odds ratio, 2.6; 95% confidence interval, 1.1–6; P = 0.02 and odds ratio, 2.6; 95% confidence interval, 1–6.7; P = 0.04). Conclusions: Laparoscopic lymphadenectomy is a safe and feasible procedure in gynecologic oncology but not free of complications. We postulate that gynecologic oncologists should be properly trained in the management of such complications and be aware of the importance of adequate hemostasis and operating time during surgery.